2011
DOI: 10.1007/s10750-011-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the morphology of beaver ponds alter downstream ecosystems?

Abstract: Differences among lake morphologies often explain variation in characteristics of lentic ecosystems. Although beaver ponds also vary in morphology, previous studies have not examined the effects of such variation on downstream ecosystems. This study evaluated downstream effects of multiple beaver ponds in the Colorado Rocky Mountains during one low and one high-flow year. Beaver pond morphology was described as the natural log transformed ratio of beaver dam height (which determines hydraulic head) to pond sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The accumulation of fine sediment and organic matter behind beaver dams is closely linked to the reduction in downstream transport and the increased input of felled or dead wood to the channel (Gurnell, 1998). Reported changes in stream or groundwater chemistry below beaver impoundments range from decreases (Correll, Jordan & Weller, 2000;Margolis, Castro & Raesly, 2001b) to increases (Klotz, 1998;Fuller & Peckarsky, 2011) in different fractions of N and P, and are typically related to increased hyporheic exchange due to longer channel residence times (Lautz, Siegel & Bauer, 2006). The reductions in N and P in our study are more substantial than often reported, but were only significant in the summer, consistent with reports by Margolis et al (2001b) and Klotz (2010).…”
Section: Changes In Habitat and Physicochemistry Due To Dam Buildingmentioning
confidence: 99%
“…The accumulation of fine sediment and organic matter behind beaver dams is closely linked to the reduction in downstream transport and the increased input of felled or dead wood to the channel (Gurnell, 1998). Reported changes in stream or groundwater chemistry below beaver impoundments range from decreases (Correll, Jordan & Weller, 2000;Margolis, Castro & Raesly, 2001b) to increases (Klotz, 1998;Fuller & Peckarsky, 2011) in different fractions of N and P, and are typically related to increased hyporheic exchange due to longer channel residence times (Lautz, Siegel & Bauer, 2006). The reductions in N and P in our study are more substantial than often reported, but were only significant in the summer, consistent with reports by Margolis et al (2001b) and Klotz (2010).…”
Section: Changes In Habitat and Physicochemistry Due To Dam Buildingmentioning
confidence: 99%
“…Even studies comparing macroinvertebrate densities between natural pools and lotic reaches have shown site-dependent effects (Herbst et al 2018;Logan and Booker, 1983). Lastly, the beaver dam itself is a habitat with a unique macroinvertebrate assemblage (Clifford, Wiley & Casey, 1993), and beaver ponds can affect macroinvertebrates downstream due to hydrologic changes altering stream temperature and nutrients (Fuller & Peckarsky, 2011a, 2011b. Lastly, the beaver dam itself is a habitat with a unique macroinvertebrate assemblage (Clifford, Wiley & Casey, 1993), and beaver ponds can affect macroinvertebrates downstream due to hydrologic changes altering stream temperature and nutrients (Fuller & Peckarsky, 2011a, 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of results in the literature associated with changes in hydraulic characteristics come from measurements upstream and downstream of dams, which does not allow for direct comparison with our study. Meentemeyer & Butler (1999) Waddington, 1990), increases in sediment storage (Butler & Malanson, 1995Green & Westbrook, 2009), and influences on downstream aquatic ecology (Fuller & Peckarsky, 2011) may also differ.…”
Section: Reach Comparison Resultsmentioning
confidence: 99%
“…Overall, it is evident that beaver dams introduce variability in depth and velocity values between reaches and that the variability cannot be solely attributed to natural differences in channel geometry and slope. These three comparisons also indicate that other impacts related to channel hydraulics, such as improvements in fish habitat heterogeneity (Kemp et al , ), riparian corridor structure and productivity (Westbrook et al , ), alterations in hydrology (Nyssen et al , ; Westbrook et al , ; Woo & Waddington, ), increases in sediment storage (Butler & Malanson, ; Green & Westbrook, ), and influences on downstream aquatic ecology (Fuller & Peckarsky, ) may also differ.…”
Section: Discussionmentioning
confidence: 99%